United States and regionalism/bilateralism - Hilaire, Alvin (IMF [Washington]US, 2003)
Examines the principle issues raised by the US emphasis on regional and bilateral trade links. Draws lessons from simulations of three free trade arrangements viz. United States/Chile, United States/Central America, and United States/Australia.